A Systematic Literature Review of Gender and Politics: Stereotypes of Gender in Political Zone on Social Media - Al Fauzi Rahmat; Galih Bagas Soesilo; Andy Arya Maulana Wijaya; Nareewan Klinrat (UIN K.H. Abdurrahman Wahid Pekalongan, 2022)
Gender issues frequently arise in political debates, and they are accompanied by negative stereotypes on social media that political opponents echo. This issue draws attention among scholars to examine of gender and political issues in social media, but we have not found any across research that can map gender and political issues in social media with the output of patterns and themes.. Therefore, this article seeks to identify trends of gender issues and politics on social media and alludes to the various stereotypes. To initiate the findings and discussion, a qualitative literature review study was used, in which data were obtained from the Academic Scopus Database involved analysis of 89 articles, which data source from 2012 to 2021 in the social science discipline. Data were managed by the NVivo 12 Plus and VOSViewer as a data analysis tool – with some of the main menus used in the NVivo 12 plus (themes classification; project maps; and group classification), other side used VOSViewer (density and overlay visualization). Our findings highlight various emerging themes proportion regarding gender issues and politics on social media. These topics have tended to increase in the current decade; newest research trends have led to studies on gender and sexuality, female leaders, anti-immigration, voice, and young women, as well as LGBT, which politics intersect—followed by some issues such as black women, Muslim women, and also white women that get involved in political debates. There are three striking main propositions: social media, politics, and gender. However, many politicians and social media users bring up the gender stereotype. In short, this research can contribute to enriching the treasures of gender issues and politics on social media.